Market Orders and Market Efficiency. - Brown, David P; Zhang, Zhi Ming (Journal of Finance, 1997)
This work compares a dealer market and a limit-order book. Dealers commonly observe order flow and collect information from multiple market orders. They may be better informed than other traders, although they do not earn rents from this information. Dealers earn rents as suppliers of liquidity and their decisions to enter or exit the market are independent of the degree of adverse selection. Introduction of a limit-order book lowers the execution-price risk faced by speculators and leads them to trade more aggressively on their information. Introduction of the book also lowers dealer profits but increases the informational efficiency of prices.